Asset Management Information System at The Health Service of Aceh Province - Rini Rizki Junita (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
As an effort to manage assets at the Aceh Provincial Health Office, an information system is needed that can handle problems in asset data collection. This research stage consists of; literature study, data collection, system analysis, system development, and report generation. Furthermore, in the development of the system used is the waterfall method or better known as the waterfall method. The design of the asset management information system software at the Aceh Provincial Office which the author designed consists of several stages, namely input design, output design, process design, control design, labor design, and cost design. The results of this study are an asset management information system built with Visual BASIC and Microsoft Office Access as databases. The conclusion that can be obtained from the analysis and design of the Asset Management Information System is that the information system will later be used to process asset data at the Aceh Health Office, namely adding, editing, searching for asset data. This system will also be equipped with displaying reports such as asset data reports and others. This application can be used as an alternative tool for processing asset data at the Aceh Health Office.